Employees’ organizational citizenship behaviour toward the environment in response to environmental management practices: A proposed mediation models - Soon-Yew, Ju; Diyana, Kamarudin; Ramayah, Thurasamy; Noor Azlinna, Azizan (Faculty of Business and Management, UiTM Pahang, 2017)
Organizational environmental management practices were acknowledged as one of the main properties in safeguarding the organizational citizenship behavior towards the environment (OCBE). Employees’ responses to organizational citizenship behavior towards the environment are subject to his or her assessment of organizational environmental management practices. The relationship between organizational environmental management practices to OCBE has been established in previous literature. However, an environmental management practices as an only construct in explaining OCBE is rather basic, accordingly this study would like to present an affective commitment towards environment construct as a mediator to bridge the gap.